Факторы возникновения УЗБЕКСКО – РУССКОЙ графической интерференции - Абдуллаева C.Н. (SCIENCE and SOCIETY, 2020)
The article is devoted to the analysis of factors of Uzbek-Russian graphic interference. The author considers the differences between the two Uzbek Latin and Russian Cyrillic as well as the unequal ratio of the principles of orthography in the Uzbek and Russian languages.